Efforts to Foster Students' Character Through a Local Culture-Based Literacy Program at MIS Darul Hikmah, Bima City - Citra Laura; Agussalam; Yayuk Kusumawati (Lembaga Bale Literasi, 2026)
This study aims to analyze efforts to shape student character through a local culture-based literacy culture at MIS Darul Hikmah in Bima City. This research uses a qualitative approach with a case study. The instruments used include observation guidelines, interview guidelines, and documentation. Data collection techniques were conducted through observation, in-depth interviews, and documentation studies, involving teachers, students, and the principal as research subjects. Data analysis techniques used the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of a local culture-based literacy culture, such as the use of folklore, regional languages, and cultural practices, contributes to the formation of student character, including honesty, responsibility, discipline, and social awareness. Furthermore, the integration of local wisdom into literacy activities increases student engagement and contextual understanding. This study concludes that a local culture-based literacy culture is an effective strategy for holistic and sustainable student character formation in the school environment.